Is adherence to the Mediterranean diet associated with good sleep duration in primary-school children? - Buja, Alessandra; Grotto, Giulia; Zampieri, Chiara; Mafrici, Simona Fortunata; Cozzolino, Claudia; Baldovin, Tatjana; Brocadello, Filippo; Baldo, Vincenzo (Frontiers in Pediatrics, 2022)
Objective The Mediterranean diet (MD) contributes to preventing numerous chronic diseases and has benefits on cognitive development. Adherence to the MD is associated with sleep quality and duration in adults and adolescents, but this association seems to have been little investigated in primary-school children. The aim of this cross-sectional study was to verify whether good sleep duration was associated with adherence to the MD. Design The study enrolled a sample of Italian primary school children. Their mothers were asked to answer an anonymous, self-administered questionnaire investigating the children's adherence to the MD (using the KidMed score) and variables related to their lifestyles, behavioral traits and socio-economic factors. Logistic regression models were developed to analyze the association between adherence to the MD, entered as the dependent variable, and adequacy of sleep duration. Setting Primary schools in Padova, Italy. Subjects 267 Italian 6-year-olds in their first year of primary school. Results The multivariate analysis showed an association between adherence to the MD and hours of sleep: for children with a good sleep duration, the odds ratio of a poor-to-moderate adherence to the MD was 0.282 (95% CI, 0.109–0.681, p < 0.05). Conclusion Ensuring an adequate sleep duration may be an important strategy for enhancing adherence to the MD. Sleep and dietary education should be included in future health promotion programs.